Reliability of pressure waveform analysis to determine correct epidural needle placement in labouring women. (17th April 2017) - Al‐Aamri, I.; Derzi, S. H.; Moore, A.; Elgueta, M. F.; Moustafa, M.; Schricker, T.; Tran, D. Q.
Summary: Pressure waveform analysis provides a reliable confirmatory adjunct to the loss‐of‐resistance technique to identify the epidural space during thoracic epidural anaesthesia, but its role remains controversial in lumbar epidural analgesia during labour. We performed an observational study in 100 labouring women of the sensitivity and specificity of waveform analysis to determine the correct location of the epidural needle. After obtaining loss‐of‐resistance, the anaesthetist injected 5 ml saline through the epidural needle (accounting for the volume already used in the loss‐of‐resistance). Sterile extension tubing, connected to a pressure transducer, was attached to the needle. An investigator determined the presence or absence of a pulsatile waveform, synchronised with the heart rate, on a monitor screen that was not in the view of the anaesthetist or the parturient. A bolus of 4 ml lidocaine 2% with adrenaline 5 μg.ml −1 was administered, and the epidural block was assessed after 15 min. Three women displayed no sensory block at 15 min. The results showed: epidural block present, epidural waveform present 93; epidural block absent, epidural waveform absent 2; epidural block present, epidural waveform absent 4; epidural block absent, epidural waveform present 1. Compared with the use of a local anaesthetic bolus to ascertain the epidural space, the sensitivity, specificity, positive and negative predictive values of waveform analysis were 95.9%, 66.7%, 98.9% and 33.3%, respectively. Epidural waveform analysis provides a simple adjunct to loss‐of‐resistance for confirming needle placement during performance of obstetric epidurals, however, further studies are required before its routine implementation in clinical practice.